Correlação entre a densidade mineral óssea e níveis séricos de cálcio, fósforo e fosfatase alcalina total em gatos após tirotoxicose experimental - Costa, Fabiano Séllos; Cardoso, Mauro José Lahm; Muniz, Lucy Marie Ribeiro [UNESP]; Vulcano, Luiz Carlos [UNESP]; dos Santos, Warley Gomes; Padovani, Carlos Roberto [UNESP] (My University, 2009)
Hyperthyroidism is and endocrinal dysfunction characterized by excessive serum concentrations of thyroid gland hormones, which can cause several effects on the bone tissue in humans and in animals. For a better characterization of thyrotoxicosis effects on bone metabolism, 16 cats were induced into hyperthyroid state. Results showed that, in some moments a major bone demineralization of the right distal radium estremity promoted an elevation of the serum levels of phosphorus and total alkaline phosphatase.
Correlation of bone mineral density and serum levels of calcium, phosphorus and alkaline phosphatase in cats after experimental thyrotoxicosis
Keywords: Bone metabolism; Cat; Hyperthyroidism; Thyrotoxicosis; Animalia